Pulmonary function, exercise capacity and physical activity participation in adults following burn - Willis, C.; Grisbrook, Tiffany; Elliott, Catherine; Wood, Fiona; Wallman, K.; Reid, S. (Pergamon, 2011)
Purpose: To determine the relationship between pulmonary function, aerobic exercisecapacity and physical activity participation in adults following burn.Methods: Eight burn injured males aged 20–55 years (%TBSA 33.3 18.7, 5.1 years 1.8 post injury), and 30 healthy adult controls participated. Pulmonary function was assessed during rest via spirometry. A graded exercise test measuring peak oxygen consumption (VO2peak) and oxygen saturation (SpO2) was conducted, and physical activity was assessed via the Older Adult Exercise Status Inventory (OA-EI).Results: No significant correlation was observed between resting pulmonary function, aerobic capacity and physical activity participation for burn injured patients or controls. Two burn injured patients presented with obstructive ventilatory defects, and one displayed a restrictive ventilatory defect. Burn injured patients had a significantly lower VO2peak ( p < 0.001) and time to fatigue ( p = 0.026), and a greater degree of oxygen desaturation ( p = 0.063, Effect Size = 1.02) during a graded exercise test. Burn injured patients reported significantly less participation in leisure-related activity > 9 METs ( p = 0.01), and significantly greater participation in work-related activity ( p = 0.038), than healthy controls.Conclusion: Compromised lung function, decreased aerobic capacity and reduced participation in leisure-related physical activity may still exist in some adults, even up to 5 years post injury. Limitations and long term outcomes of cardiopulmonary function and physical fitness need to be considered in the prescription of exercise rehabilitation programmes following burn.